Clinical Practice Guidelines of Traditional Chinese Medicine Rehabilitation for Cardiopulmonary - Working Group of Clinical Practice Guidelines of Traditional Chinese Medicine Rehabilitation for Cardiopulmonary; Xihua LIU; Xiaoxu LI; Hongyan BI; Xianliang WANG; Xin ZHENG; Yuru YANG; Shijie HAO (康复学报)
Cardiopulmonary function rehabilitation is an important part of modern rehabilitation medicine, that is the foundation of human physiological function. The level of cardiopulmonary function directly affects the quality of life and rehabilitation process of patients with cardiopulmonary dysfunction. Based on evidence-based medicine, cardiopulmonary rehabilitation can effectively improve the function of circulatory system and respiratory system, improve the quality of life of patients, and promote them return to family and social life through comprehensive and standardized assessment and comprehensive medical interventions such as medicine, exercise, nutrition, education and psychology, etc.. The main purpose of establishing the clinical practice guidelines of traditional Chinese medicine rehabilitation for cardiopulmonary is to standardize the evaluation of clinical cardiopulmonary dysfunction and rehabilitation treatment methods, so as to improve the rehabilitation effect. This guideline introduces the cardiopulmonary rehabilitation process from the scope, terms and definitions, the four diagnostic methods of cardiopulmonary diseases in TCM (syndrome differentiation and classification of heart system and lung system), cardiopulmonary function evaluation, cardiopulmonary function training. The cardiopulmonary function evaluation mainly includes the following aspects: medical history, physical examination, auxiliary examination (such as cardiac ultrasound, electrocardiogram, dynamic electrocardiogram, cardiac catheterization, lung capacity test, pulmonary ventilation function test, gas metabolism test), classification of dyspnea degree, classification of functional pulmonary disability, heart function score, evaluation of physical endurance (6-minute walking test, cardiopulmonary exercise test, fitness assessment (muscle strength, hand flexibility, balance ability assessment). The cardiopulmonary function training mainly includes the following aspects: pulmonary ventilation and lung capacity improvement training, airway clearance technology, respiratory muscle training, exercise training, acupuncture therapy, massage therapy, Taiji jar therapy, auricular therapy, guiding technique of TCM. This guideline is suitable for the rehabilitation practitioners in various rehabilitation institutions, traditional Chinese medicine hospitals or general hospitals for cardiopulmonary rehabilitation treatment, with good clinical applicability and effectiveness.